Meta-Analysis: Bullying's Effects on Anxiety and Depression in Adolescents - Amin Nur Hanida; Bhisma Murti; Didik Gunawan Tamtomo (Masters Program in Public Health, Sebelas Maret University, 2025)
Background: Bullying is a major problem worldwide. Bullying itself is defined as a condition in the form of negative and repetitive behavior, carried out by a person or group of people, the treatment is carried out deliberately and intensely with the aim of hurting physically and mentally. This study aims to analyze and estimate the magnitude of the influence of bullying on anxiety and depression in adolescents. Subject and Method: The meta-analysis was performed according to the flow of the PRISMA diagram and the PICO model. P: Adolescents, I: Bullying, C: No bullying, O: Anxiety and depression. The search for articles in this study is through databases that include PubMed, Google Scholar, Science Direct and Scopus. With keywords including: